Role of the Nuclear Receptor Corepressor 1 (NCOR1) in Atherosclerosis and Associated Immunometabolic Diseases - Geiger, Martin A.; Guillaumon, Ana T.; Paneni, Francesco; Matter, Christian M.; Stein, Sokrates (Frontiers in Immunology, 2020)
Atherosclerotic cardiovascular disease is part of chronic immunometabolic disorders such as type 2 diabetes and nonalcoholic fatty liver disease. Their common risk factors comprise hypertension, insulin resistance, visceral obesity, and dyslipidemias such as hypercholesterolemia and hypertriglyceridemia, which are part of the metabolic syndrome. Immunometabolic diseases include chronic pathologies that are affected by both metabolic and inflammatory triggers and mediators. Important and challenging questions in this context are to reveal how metabolic triggers and their downstream signaling affect inflammatory processes and vice-versa. Along these lines, specific nuclear receptors sense changes in lipid metabolism and in turn induce downstream inflammatory and metabolic processes. The transcriptional activity of these nuclear receptors is regulated by the nuclear receptor corepressors (NCORs), including NCOR1. In this review we describe the function of NCOR1 as a central immunometabolic regulator and focus on its role in atherosclerosis and associated immunometabolic diseases.